Human Rights Violations In The Agrarian Sector In The Perspective Of National Law And International Law (Case Study Of Rempang Island) - Wendra, Muhammad; Sutrisno, Andri (Social Sciences Journal, 2024)
Human Rights are a set of rights that are essentially inherent in humans. This right is natural, cannot be contested or taken away, and applies universally. Violations of human rights occur if these rights are taken away or challenged by other parties. The field of human rights violations is very broad, covering various rights possessed by humans, including in this case regarding land in the agrarian sector. Violations of human rights in the agrarian sector are basically similar to violations of human rights in other fields, the difference being the object of the right that gives rise to the human rights violation. In this case, the object in question is land in the agrarian sector. Indonesian national law and international law have slightly different perspectives regarding human rights violations in the agrarian sector. The difference is regarding control over the agrarian sector. National law has independent rights over the agrarian sector within its territory without interference from other parties outside the country, including international law. However, this form of violation of human rights, even in the agrarian sector, remains the subject of international law, as is the universal principle held by human rights law. To provide protection of rights in the agrarian sector, Indonesian national law applies the provisions of the 1945 Constitution, Law Number 39 of 1999 concerning Human Rights, and Law Number 5 of 1960 concerning Basic Agrarian Principles Regulations. Meanwhile, international law applies Convention Number 169 of the International Labor Organization (ILO), as well as the United Nations Declarations on the Rights of Indigenous Peoples (UNDRIP). Therefore, this writing aims to explain the point of view of how Indonesian national law views human rights violations in the agrarian sector through domestic regulations, as well as how international law through international instruments views human rights violations in the agrarian sector. This writing was also prepared based on normative juridical sources through Indonesian national regulations and related to international instruments. Human Rights are a set of rights that are essentially inherent in humans. This right is natural, cannot be contested or taken away, and applies universally. Violations of human rights occur if these rights are taken away or challenged by other parties. The field of human rights violations is very broad, covering various rights possessed by humans, including in this case regarding land in the agrarian sector. Violations of human rights in the agrarian sector are basically similar to violations of human rights in other fields, the difference being the object of the right that gives rise to the human rights violation. In this case, the object in question is land in the agrarian sector. Indonesian national law and international law have slightly different perspectives regarding human rights violations in the agrarian sector. The difference is regarding control over the agrarian sector. National law has independent rights over the agrarian sector within its territory without interference from other parties outside the country, including international law. However, this form of violation of human rights, even in the agrarian sector, remains the subject of international law, as is the universal principle held by human rights law. To provide protection of rights in the agrarian sector, Indonesian national law applies the provisions of the 1945 Constitution, Law Number 39 of 1999 concerning Human Rights, and Law Number 5 of 1960 concerning Basic Agrarian Principles Regulations. Meanwhile, international law applies Convention Number 169 of the International Labor Organization (ILO), as well as the United Nations Declarations on the Rights of Indigenous Peoples (UNDRIP). Therefore, this writing aims to explain the point of view of how Indonesian national law views human rights violations in the agrarian sector through domestic regulations, as well as how international law through international instruments views human rights violations in the agrarian sector. This writing was also prepared based on normative juridical sources through Indonesian national regulations and related to international instruments.